Convergence or fragmentation? Recent developments in recognition of microcredentials and their impact on higher education in Asia and the Pacific - Shingo Ashizawa; Christopher Ziguras; Akiyoshi Yonezawa (Emerald Publishing, 2024)
Purpose - This paper explores the development of microcredentials (MCs) through a regional lens, considering their implications for lifelong learning and skilled labour mobility in Asia and the Pacific. It also examines recent global initiatives led by the United Nations Educational, Scientific and Cultural Organization (UNESCO). Design/methodology/approach - The study reviews recent global initiatives aimed at developing shared definitions and principles for MCs, as led by UNESCO, taking into account the importance of existing initiatives such as the pilot project launched by the Australian government in 2022. The formalization of MCs within national education systems is also examined, with reference to frameworks developed by organizations like the European Union (EU), Australia and the Malaysia Qualifications Agency (MQA, 2020). Findings - The paper underscores the increasing attention from international organizations and governments to the development and recognition of MCs, with significant efforts in countries like Australia and pilot initiatives in New Zealand and Malaysia. However, it also highlights that many MC projects in Asia are still in their early developmental stages, emphasizing the need for further progress and formalization. Originality/value - This paper offers a unique perspective on the development of MCs in the Asia-Pacific region and their potential role in international education. It explores the prospects for MCs in international education, including student mobility and cross-border online courses. The challenge of integrating MCs into existing systems for recognizing international qualifications is discussed. Overall, the paper contributes to the understanding of MC frameworks as essential tools in the formalization of lifelong learning in the region, supported by the provided citations (OECD, 2021).